Implementasi Pembiasaan Kurikulum Ismuba Terhadap Karakter Religius Siswa di SMA Muhammadiyah 1 Bandung - Najiha Najwashihab Karsana; Imas Siti Hasanah; Adisty Zulfa Pratiwi; Akbar Abdullah; Barep Julianto Muhammad; Mukhlishah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
Religious character education faces increasingly complex challenges in the digital era and post-pandemic, particularly in maintaining the sustainability of religious practices in schools. Although religious programs are structured in the ISMUBA Curriculum in Muhammadiyah schools, few studies have examined how these practices are interpreted as lived spiritual experiences by students. This study used a qualitative approach with a hermeneutic phenomenological design involving 15 participants: 12 students, 2 ISMUBA and Islamic Religious Education (PAI) teachers, and 1 principal at SMA Muhammadiyah 1 Bandung. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using van Manen's interpretive model to identify essential themes of students' religious experiences. The results show that structured religious practices such as tadarus (recitation of the Koran), dhuha prayer, congregational prayer, religious lectures, and tahfidz (memorization of the Koran) gradually transform repetitive collective practices into intrinsic religious awareness. This process shapes what is conceptualized as habituated religiosity, namely the integration of spiritual discipline, collective experience, and reflective meaning-making. However, the sustainability of this process is influenced by digital culture and the continuity of religious practices within the family. This study recommends strengthening school-family collaboration and developing religious digital literacy to maintain the sustainability of students' religious character formation..